The Effect of Islamic Financial Inclusion on Welfare Through Religiosity Based on Tawhidi String Relations - Asep, Asep; Willy Arafah; Nirdukita Ratnawati (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Karawang Regency is a rice barn and a large industrial area with a high regional minimum wage (UMR). However, the level of welfare is still a problem for leaders, considering that welfare is always associated with asset ownership measured in rupiah units to ensure financial inclusion in the community. Karawang district is interesting for discussion. This study aims to analyse the effect of Islamic financial inclusion on welfare through religiosity based on Tawhidi string relations, data processing using quantitative data processing techniques with multiple regression analysis, and placing religiosity as an intervening. This study uses primary data collected through questionnaires with a sampling quota of 564 respondents, with the locus of karawang district. The results showed that the path coefficient (mediation) of the indirect effect of inclusion on welfare through religiosity was 0.111 with a z-value (Sobel Test) of (5.132). The direct effect of Islamic financial inclusion (X2) on welfare (Y) through religiosity (X3) is positive and significant if we look at the direct effect of the Islamic financial inclusion coefficient (X2) on improving welfare (Y) of 0.302, this indicates that there is a positive effect of financial inclusion. Sharia is towards improving people's welfare; the more people can access sharia financial inclusion, the higher the level of welfare that the community will enjoy.